Regras orçamentárias, divida pública e crescimento econômico - Carvalho Neto, Abrahão Scarcela de (2020)
This Thesis contains three essays in Public Finance. In the first essay, an analysis of the Golden Rule of Public Finance (RO) is carried out in conjunction with the New Tax Regime (NRF). RO limits credit operations to the level of capital expenditures. In turn, the NRF sets a ceiling for the evolution of primary spending. In this study, mathematical relationships are constructed to describe the different interpretations of the golden rule. Including that of RO in joint application with the NRF and the principle of budgetary balance. The general objective of the first essay is to show which rule the federal government followed, which proved unsuccessful to enable budgetary balance without increasing the debt stock. In addition, some limitations on the isolated use of each of these rules for stabilizing public debt are discussed. Another question is what is the Federal Government's debt limit? To answer this question, the second essay estimates the public debt limit that does not negatively affect economic growth, while the third essay estimates the level of indebtedness of the Federal Government that keeps the federal public debt at a sustainable level. In the second chapter, it is estimated which limit of net debt in proportion to net revenue, maintains positive economic growth rates. For this, the non-linear kink regression model proposed by Hansen (2017) was used. As a proxy for the level of indebtedness, the ratio of Public Sector Net Debt and Current Net Revenue (DLSP / RCL) is used. The result of the second test indicates that a DLSP of up to 2.5 times the RCL maintains positive impacts on economic growth. It remains to be seen whether this indebtedness limit generates a sustainable trajectory for the Federal Government's debt. This is the investigation carried out in the third essay, through the estimation of a fiscal reaction function, based on Bohn (1998), and the ethodology proposed by Hansen (2017). The results of the third trial indicate that the DLSP limit of up to 2.1 times the RCL, generates a level of sustainable indebtedness. The use of the same regression model in the second and third tests allows the comparison between the threshold values, in order to visualize a single debt limit for the Federal Government, which maintains both positive impacts on growth and the ability to settle the public debt. The joint analysis of the results of these tests indicates that a net debt of up to 2.1 times the net revenue is sustainable and maintains positive impacts on economic growth. Thus, this research aims to expand the set of information that legislators and political decision makers have to implement a debt limit that preserves good budget management.